Maximizing Human Potential: Capabilities Theory and the Professional Work Environment - Vogt, Christopher P. 1970- (2005)
Human capabilities theory has emerged as an important framework for measuring whether various social systems promote human flourishing. The premise of this theory is that human beings share some nearly universal capabilities; what makes a human life fulfilling is the opportunity to exercise these capabilities. This essay proposes that the use of human capabilities theory can be expanded to assess whether a company has organized the work environment in such a way that allows workers to develop a variety of human capabilities. This mode of analysis is put forward as a complement to the work of Mihaly Csikszentmihalyi, who has suggested that the key to promoting human well-being in the workplace is the maximization of flow experiences.
Keywords: Aristotelian ethics; Flourishing; Mihaly Csikszentmihalyi; Martha Nussbaum; purpose of business; Flow; workplace environment; human capabilities